INDEPENDENT WORK OF STUDENTS AS AN IMPORTANT FACTOR IN LEARNING ACCORDING TO THE CREDIT-MODULE SYSTEM - Hayitova Feruza Choriyarovna; Oltiboyeva Muxlisa Alisherovna; Khakimova Khonbuvi Khakimovna (Web of Journals Publishing, 2025)
This article proposes to take the European Credit Transfer System (ECTS) as a basis for organizing the educational process using the credit-modular system. The credit-modular organization of the learning process ensures the psychological development of relations between the teacher and the student. These relations contribute to the development of general educational skills and abilities, as well as the independence of students in the educational process.
Keywords: Credit-modular system, training, integration, skills, abilities, education, independent work of students.